High Reliability for Semiautomated 3D Measurements Based on Weightbearing CT Scans. (January 2022) - Kvarda, Peter; Krähenbühl, Nicola; Susdorf, Roman; Burssens, Arne; Ruiz, Roxa; Barg, Alexej; Hintermann, Beat
Background: A reliable assessment of the ankle using weightbearing radiography remains challenging. Semiautomated 3-dimensional (3D) measurements derived from weightbearing computed tomography (WBCT) scans may provide a more reliable approach. Methods: Thirty healthy individuals without any foot and ankle disorder were analyzed. We assessed 6 widely used ankle parameters (4 angles and 2 distances) using either semiautomated 3D (based on WBCT scans) or traditional 2-dimensional (2D; based on conventional radiographs) measurements. The reliability and discrepancy between both techniques were compared using intraclass correlation coefficients and the Bland-Altman method. Results: Five of 6 variables showed a lower reliability when derived from 2D measurements. The mean of 3 variables differed between the techniques: the 3D technique assessed that the talonavicular coverage angle was 18.9 degrees higher, the axial talocalcaneal angle was 5.5 degrees higher, and the talocalcaneal overlap was 3.7 mm lower when compared with 2D measurements. Conclusion: Semiautomated 3D measurements derived from WBCT scans provide more reliable information on ankle alignment compared with 2D measurements based on weightbearing radiographs. Future studies may show to what extent these parameters could contribute to current diagnostic algorithms and treatment concepts. Level of Evidence: Not applicable.